The doctrine of ultra vires under company law. a critical evaluation of it's efficacy / Mardiah Ahmad Kasim - Ahmad Kasim, Mardiah (Faculty of Law, 1987)
The ultra vires rule has a long and somewhat tangled history. The early case of Sutton’s Hospital (1 ) has generally taken to establish that a chartered corporation has all the powers of a natural person in so far as an artifical entity is physically capable of exercising them; if it misuses its powers by exceeding the objects in the charter. But it does not really throw light on the concepts which developed in the radically different circumstances of the late 18th and early 19th century (2 ).